2016
DOI: 10.4236/ojfd.2016.63019
|View full text |Cite
|
Sign up to set email alerts
|

Streaming Caused by Oscillatory Flow in Peripheral Airways of Human Lung

Abstract: Oscillatory flow facilitates gas exchange in human respiration system. In the present study, both numerical calculation and PIV (Particle Image Velocimetry) measurement indicate that, under the application of HFOV (High Frequency Oscillatory Ventilation), apparent steady streaming is caused and augmented in distal airways by the continuous oscillation, i.e., the core air moves downwards and the peripheral air evacuates upwards within bronchioles. The net flow of steady streaming serves to overcome the lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This lack of flow reversibility causes fluid to migrate to different axial locations after each cycle (Tanaka et al, 2001). Notably, Han et al (2016) analysed such streaming behaviour in a planar, symmetric double bifurcation model under CMV and HFOV conditions. They presented numerical results of the net displacement of Lagrangian (fluid) particles, where streaming strongly increased at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of flow reversibility causes fluid to migrate to different axial locations after each cycle (Tanaka et al, 2001). Notably, Han et al (2016) analysed such streaming behaviour in a planar, symmetric double bifurcation model under CMV and HFOV conditions. They presented numerical results of the net displacement of Lagrangian (fluid) particles, where streaming strongly increased at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent in-depth experimental study of the flow in a double-bifurcation (Jalal et al 2018) indicated that the mean streaming flow is small in magnitude compared to the peak oscillating flow and provided some evidence that mean streaming may decrease with increasing frequency. However, another numerical and experimental study (Han et al 2016) showed that mean streaming can transport gas over distances far further than the 'stroke' length (the distance that fluid would be transported if it simply moved as a block of fixed volume up and down the flow domain). Further, Han et al (2016) showed that multi-generation bifurcating tubes generate stronger mean streaming in their upper generations compared to single bifurcations.…”
Section: Introductionmentioning
confidence: 99%
“…However, another numerical and experimental study (Han et al 2016) showed that mean streaming can transport gas over distances far further than the 'stroke' length (the distance that fluid would be transported if it simply moved as a block of fixed volume up and down the flow domain). Further, Han et al (2016) showed that multi-generation bifurcating tubes generate stronger mean streaming in their upper generations compared to single bifurcations.…”
Section: Introductionmentioning
confidence: 99%
“…where ω = 2π/BT is the angular frequency based on breathing time (BT, where BT = 60/RR seconds), D is the tracheal diameter, and ν is the kinematic viscosity of air. RR can be altered from the resting range of 10-15 bpm during exercise (such as walking RR = 20-60 bpm [4] and yoga RR = 3-7 bpm [5]), and also in mechanical ventilation strategies, such as highfrequency oscillatory ventilation (HFOV) [6][7][8]. Further, inhalation time (IT) is about 45% of BT under normal breathing conditions [6].…”
Section: Introductionmentioning
confidence: 99%